Intersections of the arts and art therapies in the humanization of care in hospitals: Experiences from the music therapy service of the University Hospital Fundación Santa Fe de Bogotá, Colombia - Mark Ettenberger; Mark Ettenberger; Nayibe Paola Calderón Cifuentes (Frontiers Media S.A., 2022)
Humanization of care is becoming an increasingly important aspect in providing high-quality health services and the arts are more and more implemented to support and foster humanization and person-centered care efforts. Musical experiences are one of the most frequently encountered art forms in medical settings. Music therapy as a healthcare profession has a decades-long tradition in hospitals, both in inpatient and outpatient areas. However, while studies regarding the effectiveness of music therapy are on the forefront of clinical research, little attention has been paid to the profession's inherent opportunities to assist the hospitals' strategies in terms of humanization of care. Yet, the musical experiences in music therapy are especially versatile in supporting healthcare users from a holistic perspective, contributing to a more compassionate, personalized, and humanized environment. In this article, the basic pillars of humanized and person-centered care will be outlined, followed by examples of seven intersections in which the music therapy service of the University Hospital Fundación Santa Fe de Bogotá aligns with its Humanized and Compassionate Care Model. The aim of this article is to stimulate the discussion on music therapy not only as a profession that provides safe and effective treatment, but also as a therapeutic art experience that can add value for hospitals on their path toward a more humanized care culture.